LKPD Bermuatan Inquiry dan Budaya Jambi: Efektivitas dalam Meningkatkan Kemampuan Berpikir Kreatif Matematis - Sutrimo Sutrimo; Kamid Kamid; Saharudin Saharudin (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to describe the process and results of the development of mathematical LKPD and the quality of LKPD with the inquiry and culture of Jambi. This study uses the Research and Development (R & D) method that is used to produce certain products, namely developing mathematical LKPD. The development model used in this study is the ADDIE. In this development research there are two validators consisting of material expert validator test, learning design expert validator and media test, and also the user target of this product is IX grade junior high school students. The type of data taken in this study is in the form of qualitative data and quantitative data. The instruments used in the study were questionnaires and test results. The results of the study obtained an increase in students' mathematical creative thinking skills in the medium category based on the gain test seen that the score obtained was 0.4 in the medium criteria and students expressed a positive response to the developed LKPD. It can be concluded that mathematical LKPD developed very well and can improve students' creative mathematical thinking skills. Therefore this LKPD can be used by teachers and students in the learning process in the material to construct curved side spaces so that learning is more effective and obtains better learning outcomes.